1993
DOI: 10.1128/mcb.13.12.7248
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor induces phosphorylation of extracellular signal-regulated kinase 2 via multiple pathways.

Abstract: Expression of p21'n-'7, a dominant negative mutant of p2l' that blocks p2l' activation by growth factors, inhibits activation of extracellular signal-regulated kinase 2 (ERK2) by insulin and platelet-derived growth factor in rat-1 cells [A. M. M. de Vries-Smits, B. M. T. Burgering, S. J. Leevers, C. J. Marshall, and J. L. Bos, Nature (London) 357:602-604, 1992]. Here we report that expression of p21'asAsn-17 does not abolish epidermal growth factor (EGF)-induced phosphorylation of ERK2 in fibroblasts. Since EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
1

Year Published

1996
1996
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(94 citation statements)
references
References 48 publications
4
89
1
Order By: Relevance
“…The p42/p44 MAP kinase proteins are also known to be tyrosine phosphorylated following EGF stimulation (Burgering et al, 1993;Li et al, 1994). However immunoblotting total cell lysates from EGF-stimulated cells with anti-crkII, anti-crkL, or anti-MAP kinase antibodies showed that while these proteins are well expressed in ®broblasts, they do not migrate with the same mobility as the 42 kD phosphoprotein seen in v-cbl immunoprecipitates (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The p42/p44 MAP kinase proteins are also known to be tyrosine phosphorylated following EGF stimulation (Burgering et al, 1993;Li et al, 1994). However immunoblotting total cell lysates from EGF-stimulated cells with anti-crkII, anti-crkL, or anti-MAP kinase antibodies showed that while these proteins are well expressed in ®broblasts, they do not migrate with the same mobility as the 42 kD phosphoprotein seen in v-cbl immunoprecipitates (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…44,45,[62][63][64][65][66] Ras is capable of activating both Raf [67][68][69] and Mekk; 70 however, activation of the Erk pathway can also occur in the absence of Ras activation. 71 The pathways leading to Erk activation are reported to be triggered by receptor tyrosine kinases, 72,73 G-protein linked receptors, [74][75][76] PKC, 71,77,78 and calcium. 46,[79][80][81][82] Several lines of evidence suggest that the Erk pathway has an important role in modulating the survival of hematopoietic cells.…”
Section: The Ras/raf/mek/erk Signaling Kinase Cascadementioning
confidence: 99%
“…The mitogen-activated protein kinase (MAPK) family members p42 and p44 are rapidly phosphorylated upon activation of ErbB receptors by both Ras and protein kinase Cmediated pathways (24). Previous work from our group has shown a direct correlation between MAPK activation and mitogenic activity of EGF-like growth factors (15).…”
Section: Map-kinase Activation By Egf/tgfα Chimerasmentioning
confidence: 99%